Psychometric Properties of the Spirituality Index in Costa Rican Older Adults - Román-Quirós, Rafael (2024)
Objective. The aim of this study was to show evidence of the Spirituality Index for the elderly in Costa Rica. Method. 282 elders participated (M = 64 years, SD = 7.55) and data was collected in the Great Metropolitan Area between 2015 and 2016. Results. A Confirmatory Factor Analysis showed validity evidence indicating a one-dimensional structure (χ2 = 21.03, gl = 9, p = .001; CFI = .997; TLI = .994; RMSEA = .094 [.041 - .148], SRMR = .022). Reliability, as indicated by Cronbach's alpha and McDonald’s omega, demonstrated adequate internal consistency (.91). Validity evidence was also found with Temporal Life Satisfaction (r = .263, p = .001) and Psychological Well-Being (r = .173, p < .01). The results suggest that the Spirituality Index for the elderly is a satisfactory indicator to measure spirituality in Costa Rican elders.